1994
DOI: 10.1677/joe.0.1420225
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in chicken and turkey insulin-like growth factor-I (IGF-I) studied with a homologous radioimmunoassay for chicken IGF-I

Abstract: The development of a homologous radioimmunoassay (RIA) for chicken insulin-like growth factor-I (cIGF-I) and its use to investigate the developmental changes in IGF-I in the chicken and turkey is described. A double-antibody RIA has been developed using recombinantly derived cIGF-I as antigen, radiolabelled tracer and standard. The resulting immunoassay has a minimum detection limit of 0.035 ng and effective dose of 2.5 ng. Dose-response curves of chicken and turkey plasma and tissue extracts were parallel wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Plasma thyroxine (T 4 ) and tri-iodothyronine (T 3 ) were measured as previously described (Vasilatos-Younken et al 1997). Plasma insulin, IGF-I and IGF-II were measured as described by McMurtry et al (1983McMurtry et al ( , 1994McMurtry et al ( , 1998, and tissue IGF-I was measured as described by Rosselot et al (1995). McMurtry et al (1994) demonstrated that chicken IGF-binding proteins (IGFBPs) are acid-labile, so that interference of IGF-I detection by IGFBPs is not a problem using the indicated method of acid/ethanol extraction.…”
Section: Plasma Hormones and Metabolitesmentioning
confidence: 99%
“…Plasma thyroxine (T 4 ) and tri-iodothyronine (T 3 ) were measured as previously described (Vasilatos-Younken et al 1997). Plasma insulin, IGF-I and IGF-II were measured as described by McMurtry et al (1983McMurtry et al ( , 1994McMurtry et al ( , 1998, and tissue IGF-I was measured as described by Rosselot et al (1995). McMurtry et al (1994) demonstrated that chicken IGF-binding proteins (IGFBPs) are acid-labile, so that interference of IGF-I detection by IGFBPs is not a problem using the indicated method of acid/ethanol extraction.…”
Section: Plasma Hormones and Metabolitesmentioning
confidence: 99%
“…Antisera to cIGF-II were prepared in female guinea pigs utilizing a modification of a procedure previously reported (McMurtry et al 1994). Recombinantly derived cIGF-II was conjugated to keyhole limpet haemocyanin using conjugation kits supplied by Pierce Chemical Co., Rockford, IL, USA.…”
Section: Production Of Antiseramentioning
confidence: 99%
“…Antiserum from one guinea pig (40A) was selected for further validation and characterization based on its antibody titre and high affinity for cIGF-II. Anti-guinea pig -globulin serum (secondary antibody) was prepared as previously described (McMurtry et al 1994). The validation and characterization of the RIA were carried out based on the guidelines for hormone immunoassays suggested by Hafs et al (1977).…”
Section: Production Of Antiseramentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal and fetal cord blood plasmas were assayed for IGF-II concentration using an ELISA assay developed with components from R & D Systems (Minneapolis, MN). Because IGF binding proteins present in plasma may compete for IGF-II binding in ELISA, an acid/ethanol extraction of the samples was performed (40,41) to separate binding proteins from IGF-II, followed by centrifugation to remove the binding proteins. Five microliters of plasma, 2.5 L of PBS ϩ 1% BSA (fraction V), and 62.5 L of acid/ethanol (0.25 N HCl in 87% ethanol) were mixed and allowed to stand for 30 min.…”
Section: Subjectsmentioning
confidence: 99%